Upgrading Kelompok Guru Matematika Kelas Rendah di SDIT Ar-Rahmah Makassar - Syafruddin Side; Irwan Irwan; Muhammad Nusrang (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
This Community Partnership Program (PKM)conducted at SDIT Ar-Rahmah Makassar. The purposes of thisactivity are to a) improve teachers' knowledge and skills inunderstanding mathematical concepts; b) increase teachers'knowledge and skills in utilizing learning media inunderstanding mathematical concepts; and c) increase teachers'knowledge and skills in learning mathematical concepts forlow classes. The teachers' problems are a) insufficientknowledge and skills about the use of media in learningmathematics; b) insufficient knowledge and skills inunderstanding mathematical concepts; and c) lack ofknowledge and skills in utilizing media in understandingmathematical concepts. The methods used in this program aretraining, mentoring, and discussion between team andteachers. This method is carried out to 15 teachers andsubsequently evaluation and monitoring session are carried outperiodically for 3 months. The results of this study showed that1) teachers' skills and knowledge are improved; 2) teachers areable to utilize media in understanding low-grade mathematicalconcepts; and 3) publications in mass media or journals withISSN.